SUSTITUCIÓN DE LA PENA EN LA CONTRAVENCIÓN DE TRÁNSITO POR CONDUCCIÓN DE VEHÍCULOS CON LLANTAS EN MAL ESTADO, Y LA IMPLEMENTACIÓN DE MEDIDAS EDUCATIVAS - Pacheco Cuenca, Dayanna Michelle (2019)
The present thesis titled: “REPLACEMENT OF THE PENALTY IN THE CONTRAVENTION OF TRAFFIC BY DRIVING OF VEHICLES WITH TIRES IN BAD STATE, AND THE IMPLEMENTATION OF EDUCATIONAL MEASURES.”, it does reference to a thematic very important and that has generated a big variety of debates as they are the contraventions of traffic, the present work of investigation refer us to one especially the driving of a vehicle with tires in bad state, same that it has to be analysed his sanction so that this was applied satisfied with the principle of proporcionalidad to attain a harmony in the juridical field, in the present work have established me diverse aims, that refers mainly on the need to apply the principle of proporcionalidad of the penalties, likewise through this would attain obtain it application of the principle of minimum penal intervention, since in the moment to apply a sanction this has to guarantee the individual rights and in this case refer us to the right to the work that finds vulnerado with the application of sanctions of character privativas of freedom by the cometimiento of a contravention these principles and rights that find established in the Constitution of the Republic of the Ecuador, therefore when establishing penalties desproporcionales to the infringement would be vulnerando the law; considering this social problem have believed convenient to elaborate a project of reform to the Integral Organic Code Penal, to allow that it make the replacement of the penalty established for the contravention of traffic by driving of a vehicle with tires in bad state , by a penalty that this in relation to the proporcionalidad of the 6 penalties, so that it protect the right to the work and look for no only be a half penalizing rather poses in this project implement a new mechanism that will give step to a change in the society that consists in the establishment of workshops of compulsory character directed in the prevention and the education of the contraventores, measure that helped to take more consciousness on all the people, as it has showed with the happen of the years the education is the best half to attain a positive development of the society and this helped to reduce the indexes of accidents because it helped to forge people more responsible in regard to the education and security vial and the respect by the human life. For this project that has a big social importance and juridical; I look for through a replacement of the penalty, the application of a penalty acorde to the damage committed considered that we refer us to a slight contravention that does not have the spirit to cause damage, rather many times is the result the fault of economic resource or the desinformación of the norm and by this exists the need to make a change in the society, taking in consideration that in our half does not have a culture vial and through this project pretends improve the level of education in matter of education and security vial for like this form citizen more consent on the responsibility and the respect by the life and use these measures like a half of prevention in front of the accidents of traffic considering that andl Been with relates to the matter has not offered him the necessary importance that this deserves. 7 For the development of l present work used different materials and métotwo to develop the investigation and likewise made the interviews and surveys, which have served me to pose a project of legal reform to the Integral Organic Code Penal, in regard to the contravention of transito by driving of vehicle with tires in bad state, looking for guarantee the application of the principle of proporcionalidad of the penalties, when applying sanctions that do not go against of the freedom and like this allow him to the contraventor can exert his right to the work, so that through the same east can obtain the economic resource so that it can fulfil with the norm, since many of the times fall in this type of contravention by fault of these, and also goes in relation the fault of culture vial and therefore it pretends implement the continuous education that the State has to offer us in regard to education and security vial to improve the quality of citizens that are more conscious and respectful of the human life.